Development of Preschoolers’ Mathematical Patterning_x000D_ Skills Test: Validity and Reliability Study - (:unkn) unknown (My University, 2019)
Patterning knowledge and skills help to understand the order of mathematics. The use of patterns inearly mathematics learning helps children to abstract and generalize mathematical thinking and relationships.Measuring the skills of children on patterning is a prerequisite for further development in this area, but thenumber of measurement tools assessing these skills is very limited. Therefore, the aim of this study was todevelop a test for assessment of the patterning skills of preschool children and to examine its validity andreliability. As a result of the analysis, two different tests, the 26-item long form and 17-item short form, weredeveloped. The results of the current study indicated that these forms are valid and reliable for the assessment ofpreschoolers’ patterning skills.

Örüntü bilgisi matematiğin düzenini anlamakta yardımcı olur. Örüntülerin erken matematik öğreniminde_x000D_ kullanımı, matematiksel düşünce ve ilişkilerin soyutlanması ve genellenmesine yardımcıdır. Örüntüler hakkında_x000D_ becerilerin ölçülebilmesi bu alanda yapılacak geliştirme çalışmaları için bir ön koşuldur ancak bu becerileri_x000D_ değerlendiren ölçme araçlarının sayısı çok sınırlıdır. Bu nedenle bu araştırmada okul öncesi dönem çocukların_x000D_ örüntü becerilerini değerlendirmeyi amaçlayan bir testin geliştirilmesi ve bu testten elde edilen puanların_x000D_ geçerlilik ve güvenirliğinin test edilmesi hedeflenmiştir. Yapılan analizler sonucunda 26 maddelik uzun ve 17_x000D_ maddelik kısa olmak üzere 2 farklı form geliştirilmiştir. Sonuçlar, bu formların okul öncesi dönem çocukların_x000D_ örüntü becerilerini değerlendirmede kullanılabilecek geçerli ve güvenilir formlar olduğunu ortaya koymuştur.
Okul Öncesi Matematiksel Örüntü Becerileri Testinin Geliştirilmesi: Geçerlik ve Güvenirlik Çalışması